The effect of active reading software on saudi efl learners’ reading comprehension skills - Imran, Khan (2021)
The present study investigated the effects of technology-integrated instruction on reading comprehension skills of the undergraduate EFL learners at Majmaah University, Saudi Arabia. The experimental study utilized Active Reading Software (ARS) as a technological tool to examine its efficacy on reading comprehension at literal, interpretative, critical, and creative levels. The study also attempted to explore the influence of ARS instruction on learners’ attitudes towards learning reading comprehension. The variables of the study were analyzed and described based on a theoretical framework that included Schema theory, Rumelhalt (1980) and Meyer’s (2005) Cognitive Theory of Multimedia Learning (CTML). This study employed a sequential explanatory mixed-method approach following a quasi-experimental pretest posttest design for collecting the quantitative and qualitative data of the research. The study utilized 60 male participants studying English as a foreign language at Majmaah University, Saudi Arabia. Randomization procedure was used to cluster two intact groups into experimental and control groups. Quantitative data were obtained via reading achievement tests and questionnaire surveys while qualitative data were procured through semi-structured interviews. Analysis of quantitative data made use of statistical package SPSS 22, whereas qualitative data of the study were evaluated using thematic data analysis procedure. Findings of the study pointed out a significant difference in the mean scores of the experimental groups involved in the study in terms of reading achievement. The mean score of the experimental groups on reading posttest was higher than that of the control group. The conclusion was drawn from the findings that using ARS as a learning tool had significant impacts on learners’ reading achievement. The findings of this study demonstrated that ARS is an effective learning tool for enhancing reading comprehension skills since the ARS instruction focused on aspects that could improve learners’ comprehension skills. These aspects included using authentic learning materials, activation of prior or background knowledge, positive learning attitudes, interactive learning activities, individualized and stress- free learning environment. The results of the current study also showed that the participants in the experimental group performed better than the control group because they received the learning input in a conducive environment, which helped them improve their reading proficiency. In the ARS instruction, the learning materials were presented using dual-channel (auditory and visual). Thus, the nature of learning materials used in ARS reading sections and the mode of presentation have encouraged learners to involve actively in the learning process to construct meaningful information based on their prior knowledge. Furthermore, the findings also revealed positive attitudes of learners towards ARS in terms of perceived ease of use, perceived usefulness, user-friendly interface design and retention, all of which are factors that could contribute to technology acceptance and integration in the learning process. Therefore, the current study based on the findings suggests that the use of ARS as a learning tool can be effective in improving learners' reading comprehension skills and learners’ attitudes towards the adoption and integration of technology-based learning in language classes.